(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
It was hypothesised that there would be a significant difference in the Anthropometricchanges brought on by Plyometric and Circuit training for basketball players at the state level ofMADHYA PRADESH, therefore that comparison was the study’s stated goal. There were just 120 malebasketball players from MADHYA PRADESH included in the study. The players’ ages varied from 12 to16. A total of 120 participants were split evenly between the Experimental Group and the ControlGroup. Pre- and post-six-week training, anthropometric variables were measured with the sameinstruments. The Experimental group’s players trained six days per week, on alternating days(Plyometric Training on Monday, Wednesday and Friday whereas Circuit Training on Tuesday, Thursday,and Saturday). The Anthropometry was analysed to determine a mean and standard deviation. However,compared to the Control Group, the Experimental Group’s Anthropometry values were statisticallysubstantially higher.